PELATIHAN KOMUNIKASI EFEKTIF BAGI RELAWAN ANTI NARKOBA DI KOTA SURAKARTA - Herning Suryo Sardjono; Haryo Kusumo Aji (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Abstract Solo is a traffic lane for drug trafficking because of its position in the middle. Apart from being a route for drug trafficking, Solo is the city with the highest drug abuse in Central Java compared to other cities. The problem of drugs must be continuously communicated to all components of society, especially among the younger generation. For this reason, the Slamet Riyadi University Community Service Team conducts effective communication training for anti-drug volunteers as team partners so that they have the capacity to inform the younger generation about the dangers of drugs. The purpose of this service is to improve the competence (knowledge, attitudes and behavior) and integrity of Anti-Narcotics Volunteers and to increase the communication capacity of Anti-Narcotics Volunteers so that they can work well and professionally, and show maximum performance. The activities carried out are effective communication training for anti-drug volunteers. The output of this service is the journal Senadimas UNISRI. Keywords: Drugs, Effective Communication, Anti-Drug Volunteers, BNN Abstrak Solo menjadi jalur lalu lintas peredaran narkoba karena posisinya yang berada di tengah. Selain sebagai jalur peredaran narkoba, Solo adalah kota dengan penyalahgunaan narkoba tertinggi di Jawa Tengah dibanding kota -kota lainnya. Permasalahan narkoba harus terus dikomunikasikan kepada seluruh komponen masyarakat terutama para kalangan generasi muda. Untuk itu Tim Pengabdian Kepada Masyarakat Universitas Slamet Riyadi melakukan pelatihan komunikasi efektif kepada para relawan anti narkoba sebagai mitra tim agar memiliki kapasitas untuk menginformasikan kepada generasi muda tentang bahaya narkoba. Tujuan dari pengabdian ini adalah meningkatkan kompetensi (pengetahuan, sikap dan perilaku) dan integritas Relawan Anti Narkotika serta untuk meningkatkan kapasitas komunikasi Relawan Anti Narkotika agar dapat bekerja dengan baik dan profesional, serta menunjukkan kinerja maksimal. Kegiatan yang dilakukan adalah pelatihan komunikasi efektif bagi relawan anti narkoba. Luaran dari pengabdian ini adalah jurnal Senadimas UNISRI. Kata kunci: BNN, Komunikasi Efektif, Narkoba, Relawan Anti Narkoba